2004
DOI: 10.1073/pnas.0404229101
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of papillomavirus infection is enhanced by promyelocytic leukemia protein (PML) expression

Abstract: Previous studies have suggested that most papillomaviruses enter the host cell via clathrin-dependent receptor-mediated endocytosis but have not addressed later steps in viral entry. To examine these events, we followed the localization of L2 and packaged DNA after entry of infectious virions or L1͞L2 pseudovirions. Confocal microscopic analyses of HeLa cells showed a time-dependent uncoating of capsids in cytoplasmic vesicles and the accumulation of both L2 and viral DNA at distinct nuclear domains identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
280
1
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 218 publications
(301 citation statements)
references
References 57 publications
15
280
1
5
Order By: Relevance
“…It has been demonstrated that HPV33 capsids undergo a subtle conformational change after cell attachment (32), raising the possibility of cell-surface cleavage due to exposure of the N terminus of L2. Alternatively, cleavage might occur in an endocytic compartment, because the capsids clearly undergo further conformational changes, as shown by the exposure of the genome and to antibodies (5).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been demonstrated that HPV33 capsids undergo a subtle conformational change after cell attachment (32), raising the possibility of cell-surface cleavage due to exposure of the N terminus of L2. Alternatively, cleavage might occur in an endocytic compartment, because the capsids clearly undergo further conformational changes, as shown by the exposure of the genome and to antibodies (5).…”
Section: Discussionmentioning
confidence: 99%
“…Construction of CHA-L2 is described in ref. 5. To create NHA-L2, the previously described vector PMLH containing the BPV codon-modified L2 sequence was digested with the restriction endonucleases KpnI and BssHI and ligated with the annealed and likewise digested primers (5Ј-CACGCGTGGTACCGCCATGTACCCATAC-GATGTTCCAGATTACGCTAGCGCCCGCAAGAGAGT-GAAGCGCGCCAGCGCC-3Ј and its reverse complement).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations